Does preoperative insomnia explain persistent pain after breast cancer treatments? - Grén, Essi (fi=Turun yliopisto|en=University of Turku|, 2018)
Persistent pain is a common ramification of breast cancer treatments, especially breast surgery, that impairs patients’ quality of life significantly. Despite extensive research, it is still not fully understood how to predict or prevent pain. Several risk factors for persistent postoperative pain in general have been identified, such as previous pain and operation type, but these factors explain only a small proportion of the development and maintenance of persistent post-treatment pain. In recent years, sleep has received growing interest as a potential modifiable risk factor for pain for its diverse effects on physical and mental health. This study was part of a larger, prospective study conducted at the Breast Surgery Unit, Helsinki University Hospital. With 698 women, it aimed to examine preoperative insomnia as a risk factor for persistent post-treatment pain 12 months after breast cancer surgery. Insomnia was assessed as a part of a questionnaire regarding menopausal symptoms and was categorized as absence of insomnia, occasional insomnia, and nightly insomnia. Presence and intensity of pain in the operated area were assessed 12 months after surgery by a numerical rating scale (NRS) from 0 to 10. Probability of moderate to severe pain (vs. no or mild pain) was modeled using binary logistic regression. Potential confounders in the fully adjusted model were age, body mass index, previous chronic pain, preoperative pain in the operative area, axillary operation type, smoking, depressive symptoms, and menopausal symptoms. Also, the relationship between insomnia and preoperative pain was studied as preceding pain is associated with development of acute and chronic postsurgical pain. The risk of preoperative pain was over two-fold among patients with nightly insomnia compared with patients without insomnia. However, the association between preoperative insomnia and persistent postoperative pain was not statistically significant and was largely explained by menopausal symptoms. Thus, this study does not give support for preoperative insomnia as an independent risk factor for persistent post-treatment pain in breast cancer patients. The findings suggest that preoperative insomnia is tightly associated with preoperative pain, but other factors appear to play a more prominent role in the transition to persistent pain. More longitudinal research is needed on the subject with validated insomnia questionnaires as well as on the role of menopausal symptoms in pain persistence among breast cancer patients.